(3GdbQGQ GdEOGQi hGdWYf ajI ai VhA JZjQ GdXQha (B: s (3OQGSI ebGQfI (B/ s - (3eMehO MeOi YHGS YWjg s; (3eMeO eMeO HOQGf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JfGhdJ GdQSGdI ef NdGd efgL JMdjdi ebGQf OQGSI ehVhY GdbQGQ GdEOGQi hGdWYf ajg ai VhA JZjQ GdXQha ai aQfSG heUQ ef NdGd aUd JegjOi hHGHjf eJYGbHjf MjK JfGhdJ GdeHOC GdYGe ai bjGS eTQhYjI GdbQGQ GdEOGQi heGjQO Ydjg ef BKGQ hJfGhd GjVG OQGSI CKQ JZjQ GdXQha GdhGbYjI hGdbGfhfjI Ydi eTQhYjI GdbQGQ GdEOGQi hCKQ JZjQ XQha EUOGQ GdbQGQ (B- (3GdhGbYjI hGdbGfhfjI (B- (3Ydi GdWYf ai GdbQGQ GdEOGQi hGNJJeJ GdQSGdI HeG JhUd Edjg GdHGMK ef fJGFL heGGbJQMg GdHGMK ef JhUjGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B768-788s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdWYf ai GdbQGQ GdEOGQi s; (3GdbQGQ GdEOGQis; (3JZjQ GdXQhas; (3eTQhYjI GdbQGQ GdEOGQj s; (3GdbQGQGJ GdaQOjI s; (3XQha GdhGbY GdGSJKfGFjI s; (3GdbQGQGJ GdEOGQjI GddGFMjI s; (3GdXQha GdbGfhfjI s; (3eLQjGJ fXQ GdWYfs; (3XQha GdhGbY GdYGOjIs; (3ehba GdfXGe GdbGfhfj GdaQfSj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes